Animasi Pembelajaran IPA Menggunakan Metode Simulasi untuk Siswa Kelas VIII UPTD SPF SMP Negeri 1 Kuala Baru Aceh Singkil - Ananda, Meri; Khair, Ummul; Lestari, Yuyun Dwi (Sublim: Jurnal Pendidikan, 2024)
This study aimed to analysis and discover the potential and condition of interactive learning media of IPA class VIII which has been used by SMP in aceh singkil district, produce interactive learning media that according to the SMP class VIII IPA using method based animation flash using Adobe Flash, analyze the attractiveness of interactive learning media of SMP class VIII based animation flash using Adobe Flash.The research used research and development approach. The study was conducted SMP 1 Kuala baru aceh singkil, collected data used test and questionnaires. Data were analyzed quantitively and qualitatively.The conclusion of the study ware: (1) interactive multimedia could be developed for learning material that are difficult for students of class VIII IPA aceh singkil kuala baru, that’s was science material, (2) produced interactive multimedia products validated by media, material, and design experts, (3) the product uses multimedia interactive is expected to be effective in raising students average scores.